Glycerol Acetylation over Organic‐Inorganic Sulfonic or Phosphonic Silica Catalysts. Issue 17 (19th June 2017) - Beejapur, Hazi A.; La Parola, Valeria; Liotta, Leonarda F.; Testa, Maria Luisa
Abstract: Silica based catalysts containing organic framework with both amino and sulfonic or phosphonic functions were synthesized, characterized and tested in esterification reaction of aliphatic polyalcohols as glycerol. The aim of the research was to study the relations between the structure and the activity of the materials focusing on both, the effect of the amino group and the influence of aliphatic or aromatic chain on the acidic active sites. The effects of the sulfonic and phosphonic functions and the morphology of SiO2, amorphous or mesostructured Santa Barbara Amorphous (SBA‐15), were also addressed. The materials were compared with some commercial catalysts, showing good performances in term of activity and stability. Fresh and spent specimens were analyzed by means of thermo‐gravimetrical analysis (TGA), X‐ray photoelectron spectroscopy (XPS), small angle X‐ray scattering (SAXS), FT‐Infrared spectroscopy (FT‐IR) and acid capacity measurements. The best performances in terms of glycerol conversion and selectivity to acetins were achieved in presence of the sulfonic function linked to the amino‐propyl SiO2, while the highest stability during three catalytic cycles was registered for the analogous SBA‐15 sample. Abstract : Solid acid materials for by–product transformations: Silica based catalysts containing organic framework with both amino and sulfonic or phosphonic functions were prepared as catalysts for the transformation of glycerol into value‐added products. Both the type of acidic function and the morphology of the support play an important role in the catalytic performance.